IoT-Enabled Smart Agriculture: a Pathway to Nigeria's Economic Recovery and Sustainable - Dickson, Solomon Makasda; Ogbonnaya Okechukwu UKEGBU (RADINKA JAYA UTAMA PUBLISHER, 2024)
As Africa's largest economy, Nigeria has the potential to become a leading nation in economic recovery and sustainable development. The rapid growth of the Internet of Things (IoT) and the introduction of smart agriculture present an opportunity for Nigeria to create meaningful economic growth and improve livelihoods. This study is aimed at examining the potential of IoT-enabled smart agriculture to provide a pathway to economic recovery and sustainable development in Nigeria. The specific objectives are to review an overview of Nigeria's current agricultural sector and the challenges it faces, including security, privacy, cost, data management, energy, lack of access to knowledgeable farming techniques, and oversight of land use. The method adopted in this study was the incremental descriptive model (IDM). It then provides the potential solutions of IoT-enabled smart agriculture to address these challenges and provide Nigeria's agricultural sector with the resources it needs to both increase yields and improve environmental sustainability. Then it outlines the potential economic impacts of IoT-enabled Smart Agriculture, including increased productivity, improved farmers' access to modern technologies and services, and increased job opportunities for rural populations. It also focuses on the potential of the system to reduce greenhouse gas emissions, providing crucial support for Nigeria's ambitious climate ambitions. In conclusion, with the right policies and measures put in place, the system can provide a pathway for economic growth and environmental sustainability. Moreover, the potential of the system to reduce poverty and provide job opportunities for rural populations offers a crucial opportunity for Nigeria to remain competitive in the global economy while simultaneously supporting its environmental goals.